2007
DOI: 10.1111/j.1600-0668.2007.00497.x
|View full text |Cite
|
Sign up to set email alerts
|

Inverse modeling methods for indoor airborne pollutant tracking: literature review and fundamentals

Abstract: The proposed method can help identify contaminant source characteristics (location and release time) with limited sensor outputs. This will ensure an effective and prompt execution of building management strategies and thus achieve a healthy and safe indoor environment. The method can also help design optimal sensor networks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
69
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(69 citation statements)
references
References 42 publications
0
69
0
Order By: Relevance
“…The method, named as the adjoint probability method, was first proposed by Wilson (1999 and2001) to track groundwater pollutant sources. The method can, in theory, identify pollutant source location, flux, and release time with least priori information, and is faster than other inverse modeling algorithms (Liu and Zhai 2007a). One key concept (or variable) in this method is the location probability density function (LPDF), which describes the possibility of a contaminant parcel released from a source location s x at 0 t = to reach an observation/ sensing location o x in the…”
Section: Principles Of Probability-based Inverse Modeling Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…The method, named as the adjoint probability method, was first proposed by Wilson (1999 and2001) to track groundwater pollutant sources. The method can, in theory, identify pollutant source location, flux, and release time with least priori information, and is faster than other inverse modeling algorithms (Liu and Zhai 2007a). One key concept (or variable) in this method is the location probability density function (LPDF), which describes the possibility of a contaminant parcel released from a source location s x at 0 t = to reach an observation/ sensing location o x in the…”
Section: Principles Of Probability-based Inverse Modeling Methodsmentioning
confidence: 98%
“…Inverse modeling of advection-dispersion problems has been studied for decades. A few modeling theories and methods have been developed and applied to predict atmosphere and ground water pollutions, as reviewed by Liu and Zhai (2007a). For indoor air quality applications, three studies have been found in the literature: Sohn et al (2002 and2003), Zhang and Chen (2007), and Vukovic and Srebric (2007).…”
Section: Principles Of Probability-based Inverse Modeling Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This assessment requires information about number of sources, their locations, emission rates, time, and duration of releases. However, in most of the realistic events, the difficulty increases when distributed contaminant sensor networks detect concentrations over threshold value but have no particular idea about the releases including their origin (LIU and ZHAI, 2007). This necessitates the development of a methodology that can help in identifying potential contaminant sources from limited concentration measurements.…”
Section: Introductionmentioning
confidence: 99%
“…indoor environment with passive or active airflows [7], [8]. These contaminant events could be the result of an accident, such as carbon monoxide (CO) leakage from a malfunctioning furnace, or a terrorist attack.…”
mentioning
confidence: 99%